Atipikus szerződések Magyarországon és Szerbiában - Papp, Tekla; Dudás, Attila (Debreceni Jogi Műhely, 2013)
The paper analyzes the notion and types of atypical contracts, primarily in the Hungarian and Serbian law, but also in wider, European perspective. The analysis sheds light on the different terms used in different legal systems to denominate contracts that do not fit explicitly into the range of nominate contracts, that is into the range of contract-types envisaged by the civil code or code of obligations, respectively. According to the Hungarian legal literature, all civil law contracts are divided into two main groups: nominate and innominate contracts. The former group is further divided into the categories of typical and atypical contracts, while the latter into the categories of mixed contracts and de facto innominate contracts. The authors conclude that there is a tendency in Europe, both in the jurisprudence, the legislation and the application of law, to create a unified and coherent law of contracts, which affects the range of atypical contracts as well. Most notably, the Draft Common Frame of Reference, the normative proposal of the Study Group on a European Civil Code and the Research Group on EC Private Law (Acquis Group), contains model rules on franchise, timesharing, commercial agency and treatment contracts, just as rules on electronic commerce, on the one hand. The legislation of the European Union, on the other, aims at the highest possible level of harmonisation of laws which, from the aspect of protection of consumers and competition law, affects the range and statutory content of atypical contracts. Finally, the paper refers to a series of decisions of the Court of Justice of the European Union that tackle certain features of the atypical contracts, whereby the Court in the determination of issues of contract law applies a rather functional approach.